2017
DOI: 10.1155/2017/6419439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bedtime Periocular Warming on Sleep Status in Adult Female Subjects: A Pilot Study

Abstract: Several studies have reported that suitable manipulation of human skin or body temperature can lead to improved sleep. To clarify the effect of skin warming on human sleep, 38 female subjects, who occasionally had difficulty with falling asleep, were studied. The participants underwent two experimental sessions, which were carried out in two consecutive follicular phases and randomly crossed over. The participants wore hot or sham eye masks in one 14-day session. The first half of each 14-day session was desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
(18 reference statements)
2
9
1
Order By: Relevance
“…However, it is not clear which location on the human skin is most effective to promote sleep. Previous 22 , 23 studies and present study have showed that appropriate periocular skin warming has favorable effects on sleep. We postulate that the periocular skin region might be regarded as one closest regions of the eyes which is directly connected to the brain.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, it is not clear which location on the human skin is most effective to promote sleep. Previous 22 , 23 studies and present study have showed that appropriate periocular skin warming has favorable effects on sleep. We postulate that the periocular skin region might be regarded as one closest regions of the eyes which is directly connected to the brain.…”
Section: Discussionsupporting
confidence: 67%
“…We have previously developed a disposable heat- and steam generating sheet (HSG-sheet) which can safely and easily manipulate the local skin temperature (e.g., the periocular 20 – 24 , neck 23 , and abdominal 25 skin region) at home. Our studies has reported that periocular skin warming before bedtime improved the subjective sleep quality 22 , 23 and increased the electroencephalography (EEG) delta power 23 during the first half of the sleep episode in adults with mild difficulty falling asleep. Recently, we have demonstrated that periocular skin warming increased the distal skin temperature in the hand and foot, which indicated enhancement of the physiological heat loss process 24 .…”
Section: Introductionmentioning
confidence: 88%
“…Sleep is closely tied to the circadian rhythm of core body temperature ( Lack & Lushington, 1996 ). To date, researchers have explored passive body heating through the skin to decrease sleep onset latency ( Raymann, Swaab, & Van Someren, 2007 ) and warming of the periocular skin to improve subjective sleep quality ( Sakamoto et al, 2017 ) and even increase delta power during sleep ( Igaki et al, 2018 ). The authors of the latter study developed a heat- and steam-generating sheet to warm the skin, either around the eyes, neck or abdomen, which proved effective for improving sleep quality.…”
Section: Simulating Worlds Through Sensory Stimulationmentioning
confidence: 99%
“…We developed a disposable heat- and steam-generating sheet (HSG) to safely and easily warm local skin regions and induce mental and physical relaxation (e.g., the periocular 1618 , neck 17,19 , and abdominal skin regions 20 ). Recently, warming of the periocular skin at bedtime has been reported to improve the subjective sleep quality 16,17 and increase the delta power during sleep 17 in adults with mild difficulty falling asleep. Previous observations that warming the abdominal skin region increases the skin blood flow and temperature in the feet and fingers 20 may indicate that periocular skin warming influences sleep through a similar heat loss process via distal skin regions, as reported in previous clinical and intervention studies.…”
Section: Introductionmentioning
confidence: 99%